Indar sabhā kī rivāyat - Ḥusain, Muḥammad Šāhid (Qaumī Kaunsil barāʾe Faroġ-i Urdū Zabān, Vizārat-i Taraqqī-i Insānī Visāʾil, Ḥukūmat-i Hind, 2008)
Study of Indara Sabhā, a play by Amānat, 1816-1858, Urdu author
Includes bibliographical references (p. [337]-343). - In arab. Schrift, Urdu. - Reprint. Originally published, 1984
Keywords: Amānat 1816-1858